Psychosocial correlates of breast self -examination (BSE) among Malaysian Malay female factory workers - Suri Nurtharwa Bt. Tuan Kamauzaman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The purpose of this study was to determine the psychological predictors of breast selfexamination (BSE) among Malaysian Malay female factory workers. The predictor variables were susceptibility, severity, benefits and barriers, from the Health Belief Model (HBM) and health locus of control. The hypotheses were: (1) the stronger the perceived susceptibility to breast cancer, the more likely women will perform BSE, (2) the more severe the perceptions of breast cancer, the more likely women will perform BSE, (3) the more benefits perceived in performing BSE, the more likely women will perform BSE, (4) the fewer barriers perceived in performing BSE, the more likely women will perform BSE and (5) the stronger the internal health locus of control, the more likely women will perform BSE. It was also hypothesized that social support would moderate the relationship between the HBM variables, health locus of control and BSE. Participants were a convenience sample of 135 Malay female factory workers, aged between 19 to 48 years old (M= 29.61) employed in Penang and Selangor. Data were collected using self-administered questionnaires which included validated back-translated measures such as the Health Belief Model Scale (Champion 1993), the Multidimensional Health Locus of Control Scale (Wallston, Wallston & DeVellis, 1978), the Medical Outcomes Study- Social Support Survey (MOS-SS) (Sherbourne, C.D., & Stewart, A.L. 1991) and items on demographic characteristics and other health screening behaviors. Results indicate revealed that women who were married, have children, have done clinical breast examination and Pap smear and those with strong perceived benefits of BSE were more likely to practice BSE. Results were discussed in terms of its implications for designing BSE educational interventions. The limitations and recommendation for future research were also presented.